Persiapan Peningkatan Kemandirian dan Produktivitas ODGJ Melalui Edukasi Perawatan Diri, Social Skill Trainning, dan Psikoedukasi Keluarga pada Fase Recovery - Fitria, Dian; Setyaningsih, Tri; Silalahi, Malianti; Rosliany, Nia; Juliani, Enni; Dameria, Dameria (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2025)
The recovery phase is an important phase for patients to be able to return to society and recover, be independent and productive. Failure in this phase results in relapse and readmission of the patient to health services. Recovery is not just a patient going to the hospital and taking medication, but it is more complex than that, it requires support from the family. Education on the importance of self-care, communication and social interaction for patients and family psychoeducation are the intervention packages provided in this activity program. This program aims to increase patient self-esteem so that they can communicate and interact socially, as capital to return to being independent and productive in society. This activity was carried out at social rehabilitation in Central Jakarta for all 20 patients and families. The method used is to provide education containing self-care knowledge for patients and family psychoeducation. The results of this activity increase the patient's knowledge and ability to care for themselves, communicate and social interaction, followed by an increase in the family's ability to care for the patient and carry out stress management. This program hoped that through this activity patients can recover, reduce patient recurrence rates, increase patient independence and productivity with support from family and community